SLAMF1-derived peptide exhibits cardio protection after permanent left anterior descending artery ligation in mice - Olsen, Maria Belland; Kong, Xiang Yi; Louwe, Mieke C.; Lauritzen, Knut H.; Schanke, Ylva; Kaasbøll, Ole Jørgen; Attramadal, Håvard; Øgaard, Jonas; Holm, Sverre; Aukrust, Pål; Ryan, Liv; Espevik, Terje; et al. (Frontiers in Immunology, 2024)
Acute myocardial infarction (MI) results in tissue damage to affected areas of the myocardium. The initial inflammatory response is the most damaging for residual cardiac function, while at later stages inflammation is a prerequisite for proper healing and scar formation. Balancing the extent and duration of inflammation during various stages after MI is thus pivotal for preserving cardiac function.Recently, a Signaling lymphocytic activation molecule 1 (SLAMF1)-derived peptide (P7) was shown to reduce the secretion of inflammatory cytokines and protected against acute lipopolysaccharide-induced death in mice. In the present study, we experimentally induced MI by permanent ligation of the left anterior descending artery (LAD) in mice, and explored the beneficial effect of immediately administering P7, with the aim of dampening the initial inflammatory phase without compromising the healing and remodeling phase. Blood samples taken nine hours post-LAD surgery and P7 administration dampened the secretion of inflammatory cytokines, but this dampening effect of P7 was diminished after three days. Echocardiography revealed less deterioration of cardiac contraction in mice receiving P7. In line with this, less myocardial damage was observed histologically in P7 treated mice.In conclusion, the administration of a SLAMF1-derived peptide (P7) immediately after induction of MI, reduces the initial myocardial inflammation, reduces infarct expansion, and leads to less deterioration of cardiac contraction.